Growing Together or Growing Apart? A Village Level Study of the Impact of the Doha Round on Rural China - Kuiper, Marijke; van Tongeren, Frank (World Bank, Washington, DC, 2012)
Most studies of the opening of the Chinese economy focus at the national level. The few existing disaggregated analyses are limited to analyzing changes in agricultural production. The authors use an innovative village equilibrium model that accounts for nonseparability of household production and consumption decisions. This allows them to analyze the impact of trade liberalization on household production, consumption, and off-farm employment, as well as the interactions among these three aspects of household decisions. They use the village model to analyze the impact of price changes and labor demand, the two major pathways through which international trade affects households. Analyzing the impact of trade liberalization for one village in the Jiangxi province of China, the authors find changes in relative prices and outside village employment to have opposite impacts on household decisions. At the household level the impact of price changes dominates the employment impacts. Comparing full trade liberalization and the more limited Doha scenario, reactions are more modest in the latter case for most households, but the response is nonlinear to increasing depth of trade reforms. This is explained by household-specific transaction (shadow) prices in combination with endogenous choices to participate in the output markets. Rising income inequalities are a growing concern in China. Whether trade liberalization allows incomes to grow together or to grow apart depends on whether one accounts for the reduction in consumption demand when household members migrate. Assessing the net effect on the within-village income distribution, the authors find that poorer households that own draught power gain most from trade liberalization. The households that have to rely on the use of own labor for farm activities and are not endowed with traction power, nor with a link to employment opportunities in the prospering coastal regions, have fewer opportunities for adjustment.